2022
DOI: 10.1021/acs.jpcc.1c10638
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ordered TiMC and TiMCT2 (M = Cr and Mo; T = O and S) MXenes as High-Performance Anode Materials for Lithium-Ion Batteries

Abstract: First-principles calculations were used to assess the potential of ordered TiMC and TiMCT2 (M = Cr, Mo; T = O, S) monolayers as high-performance anode materials of lithium-ion batteries (LIBs). The predicted results reveal that Li can easily adsorb on the surfaces of TiMC monolayers, especially on the TiMCT2 monolayers. The density of states analysis shows that TiMC (M = Cr and Mo) and TiCrCO2 monolayers exhibit metallicity with good intrinsic advantages for the application of LIBs. The calculated lowest Li-io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…The noted storage capacity is larger than the reported Na host materials for SIBs such as Na x VS 2 (232 mA h g À1 ), Li x TiCrCO 2 (373 mA h g À1 ), Na x W 2 C (144 mA h g À1 ), Na x Nb 2 C (271 mA h g À1 ), Na x SnSe 2 (387 mA h g À1 ) and Na x YS 2 (350 mA h g À1 ). [56][57][58][59][60][61] Front and side snapshots of the optimized structures of Na x SnS at x = 0.11, 0.22, 0.55, 1.00, 1.55, and 2.00 are shown in Fig. 4.…”
Section: Voltage and Na Storage Capacitymentioning
confidence: 99%
“…The noted storage capacity is larger than the reported Na host materials for SIBs such as Na x VS 2 (232 mA h g À1 ), Li x TiCrCO 2 (373 mA h g À1 ), Na x W 2 C (144 mA h g À1 ), Na x Nb 2 C (271 mA h g À1 ), Na x SnSe 2 (387 mA h g À1 ) and Na x YS 2 (350 mA h g À1 ). [56][57][58][59][60][61] Front and side snapshots of the optimized structures of Na x SnS at x = 0.11, 0.22, 0.55, 1.00, 1.55, and 2.00 are shown in Fig. 4.…”
Section: Voltage and Na Storage Capacitymentioning
confidence: 99%
“…and Mo; T, O. and S) monolayers show good metallic behavior with better benefits for Li-ion battery applications. The as-obtained lowest Li-ion diffusion barriers of pure TiCrC and TiMoC monolayers onto the Ti surface were 0.031 and 0.041 eV . Similarly, surface halogenated Ti 3 C 2 MXenes were investigated using first principle and density function theory with van der Waals correction, which revealed that surface halogenated Ti 3 C 2 MXenes exhibit high metallic conductivity, low diffusion barrier, and storage capacity.…”
Section: Mxene-based Electrodes For Li-ion Batteriesmentioning
confidence: 94%
“…The as-obtained lowest Li-ion diffusion barriers of pure TiCrC and TiMoC monolayers onto the Ti surface were 0.031 and 0.041 eV. 88 Similarly, surface halogenated Ti 3 C 2 MXenes were investigated using first principle and density function theory with van der Waals correction, 32 which revealed that surface halogenated Ti 3 C 2 MXenes exhibit high metallic conductivity, low diffusion barrier, and storage capacity. The surface chlorination of Ti 3 C 2 led to expansion of interlayer spacing, leading to enhancement in Li-ion accessibility and fast charge−discharge rate.…”
Section: Role Of Surface and Its Modification In Mxenementioning
confidence: 99%
“…28 A number of Sfunctionalized MXenes have been reported as electrode materials for potential metal ion batteries due to their lower diffusion barrier and higher storage capacity. [29][30][31][32][33][34][35][36][37] Luo et al investigated the nitrogen reduction reaction (NRR) of Fe adsorbed on Ti 3 C 2 O 2 or N/F/P/S/Cl-doped Ti 3 C 2 O 2−x MXene and found that F and S doping can reduce the energy barrier of the rate-determining step. 38 Bae et al reported a new structural phase of Sc 2 CO 2 containing C3 trimers converted from the hexagonal carbon of the typical trigonal MXene phase, with two very active anion electrons located in the voids between C3 trimers.…”
Section: Introductionmentioning
confidence: 99%